Gender differences in perception of workplace sexual harassment among future professionals - Amitav Banerjee; Bhavana Sharma (Industrial Psychiatry Journal, 2011)
Background: Indian society is in a stage of rapid social transition. As more women enter the workforce, stresses vis-à-vis the genders are to be expected in patriarchal society to which most of our population belongs. Earlier studies in Western societies have revealed gender differences in perception of what constitutes sexual harassment. Aim: Elicit gender differences, if any, in the workplace sexual harassment among future professionals. Settings and Design: A cross-sectional study among the students of professional colleges. Materials and Methods: A total of 200 students of both sexes were randomly selected from four professional colleges. Data collection was done on a structured questionnaire by interview. Statistical Analysis: Internal consistency of the questionnaire was tested by Crohnbach′s α coefficient. Associations between gender and perceptions were explored with Chi-square, Odds Ratio with 95% confidence interval, where applicable. Results: The differences in perception on what constitutes sexual harassment among the genders were statistically significant on many measures (P<0.01). Conclusions: Men and women differ in their awareness as to what constitute sexual harassment. Men were more lacking in awareness regarding sexual harassment.